Exploring the Anthropometric, Cardiorespiratory, and Haematological Determinants of Marathon Performance - Christou, Georgios A.; Pagourelias, Efstathios D.; Deligiannis, Asterios P.; Kouidi, Evangelia J. (Frontiers in Physiology, 2021)
Aim: We aimed to investigate the main anthropometric, cardiorespiratory and haematological factors that can determine marathon race performance in marathon runners. Methods: Forty-five marathon runners (36 males, age: 42±10 years) were examined during the training period for a marathon race. Assessment of training characteristics, anthropometric measurements, including height, body weight (n=45) and body fat percentage (BF%) (n=33), echocardiographic study (n=45), cardiopulmonary exercise testing using treadmill ergometer (n=33) and blood test (n=24) were performed. We evaluated the relationships of these measurements with the personal best marathon race time (MRT) within a time frame of one year before or after the evaluation of each athlete. Results: The training age regarding long-distance running was 9±7 years. Training volume was 70(50-175) km/week. MRT was 4:02:53±00:50:20 h. The MRT was positively associated with BF% (r= 0.587, p=0.001). Among echocardiographic parameters, MRT correlated negatively with right ventricular end-diastolic area (RVEDA) (r= -0.716, p<0.001). RVEDA was the only independent echocardiographic predictor of MRT. With regard to respiratory parameters, MRT correlated negatively with maximum minute ventilation indexed to body surface area (VEmax/BSA) (r= -0.509, p= 0.003). Among parameters of blood test, MRT correlated negatively with haemoglobin concentration (r = -0.471, p=0.027) and estimated haemoglobin mass (Hbmass) (r= -0.680, p=0.002). After performing multivariate linear regression analysis with MRT as dependent variable and BF% (standardized β=0.501, p=0.021), RVEDA (standardized β= -0.633, p=0.003), VEmax/BSA (standardized β=0.266, p=0.303) and Hbmass (standardized β= -0.308, p=0.066) as independent variables, only BF% and RVEDA were significant independent predictors of MRT (adjusted R2=0.796, p<0.001 for the model). Conclusions: The main physiological determinants of better marathon performance appear to be low BF% and RV enlargement. Upregulation of both maximum minute ventilation during exercise and haemoglobin mass may have a weaker effect to enhance marathon performance.